Effectiveness of structured teaching programme on polycystic ovarian syndrome among undergraduate female students in colleges of Pokhara - Gurung, Amrita; Gurung, Bishnu (Journal of Gandaki Medical College-Nepal, 2026)
Introduction: Polycystic ovarian syndrome (PCOS) is a common hormonal disorder affecting 1 in 10 women of reproductive age, causing irregular periods, ovarian cysts, weight gain and fertility issues. Due to inadequate awareness, many women remain undiagnosed. This study aimed to assess the effectiveness of structured teaching programme on polycystic ovarian syndrome among undergraduate female students in colleges of Pokhara.Methods: A pre-experimental one group pre-test post-test research design was used among 141 undergraduate female students in selected colleges under Tribhuvan University of Pokhara by using probability stratified random sampling technique. Data were collected through structured self-administered questionnaire where pre-test and post-test was done on in a gap of 28 days of teaching programme. Analysis was performed using SPSS Version 16, employing descriptive statistics (frequency, percentage, mean, standard deviation) and inferential statistics (paired t-test and chi-square test).Results: The findings of the study revealed that 47(33.3%) of students had inadequate knowledge before teaching programme, which improved to 67(47.5%) with adequate knowledge after teaching programme. The mean knowledge score before and after teaching programme was 43.81±9.31 and 56.20±12.47 respectively. The alternative hypothesis was accepted, indicating a significant improvement. Furthermore, a significant association was also found between students’ knowledge levels and their faculty (p = 0.032 pretest).  Conclusions: The study concluded that structured teaching programme on polycystic ovarian syndrome was effective, as it significantly improved students' knowledge. To enhance students’ understanding of Polycystic Ovarian Syndrome (PCOS), the college authorities can incorporate PCOS education into the college curriculum, organize regular educational programs, video-assisted teaching sessions, lectures and interactive discussions.